2023
DOI: 10.3389/pore.2023.1611033
|View full text |Cite
|
Sign up to set email alerts
|

CircRNA: A new class of targets for gastric cancer drug resistance therapy

Abstract: Gastric cancer (GC) is one of the most common malignancies worldwide. Patients with advanced GC need palliative care to ensure survival. This includes the use of chemotherapy agents, such as cisplatin, 5-fluorouracil, oxaliplatin, paclitaxel, and pemetrexed, as well as targeted agents. However, the emergence of drug resistance evidence in poor patient outcomes and poor prognosis is a motivation to determine the specific mechanism of drug resistance. Interestingly, circular RNAs (circRNAs) play an important par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…It has been revealed that circRNAs cannot only affect the progression of gastrointestinal cancer, but also participate in their chemoresistance ( 102 ). A number of circRNAs have a role in drug resistance in GC, such as circ 0008253 and circ_0091741 ( 103 , 104 ).…”
Section: Biological Functions Of Exosomal Circrnas In Gastrointestina...mentioning
confidence: 99%
“…It has been revealed that circRNAs cannot only affect the progression of gastrointestinal cancer, but also participate in their chemoresistance ( 102 ). A number of circRNAs have a role in drug resistance in GC, such as circ 0008253 and circ_0091741 ( 103 , 104 ).…”
Section: Biological Functions Of Exosomal Circrnas In Gastrointestina...mentioning
confidence: 99%
“…Circular RNA (circRNA) has a great advantage in becoming a biomarker for human diseases, including cancer. [ 5,6 ] CircRNA plays a vital part in cancer progression and shows great potential in cancer diagnosis, prognosis and treatment. [ 7 ] CircRNA can be used as an oncogene to promote cancer progression, [ 8 ] or as a tumor suppressor to inhibit the malignant biological behaviors of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Circular RNAs (circRNAs) are a special kind of noncoding RNA with a closed loop structure and extremely stable expression (10)(11)(12). The important regulatory effect of circRNA on cell biological functions in human disease has been confirmed (13)(14)(15)(16). For example, it was found that circ-HIPK2 could promote myocardial oxidative injury by increasing cell apoptosis and autophagy (17).…”
Section: Introductionmentioning
confidence: 99%